THE AUTOMATED MANUFACTURING COMPLEX FOR THE FORMATION OF THE RECHARGEABLE BATTERY OF THEIR MASS PRODUCTION - Dzenzerskyi, V. O.; Skosar, V. Yu.; Buriak, O. O.; Dzenzerskyi, D. V.; Syrenko, M. V.; Lisnychii, V. M.; Burylov, S. V. (Science and Transport Progress, 2008)
A computerized manufacturing complex providing storage batteries formation and charging in flow line production is proposed. The complex enables use of up-to-date technologies in storage batteries formation and charging ensuring accelerated formation or charging by high-rate pulse currents based on battery water tank cooling system.